Hubungan Daya Tilik dan Self Stigma Terhadap Kepatuhan Minum Obat Pada Pasien Skizofrenia : A Cross-Sectional Study - Nurul Amna; Khaira Rizki; Abqariah; Ellyza Fazlylawati (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
Non-compliance with taking medication in schizophrenia patients can have various negative impacts, both for the patient and the surrounding environment. To reduce this negative impact, it is very important to pay attention to medication compliance in patients with schizophrenia and know the things that cause this compliance. The aim of this study was to determine the relationship between insight factors and self-stigma on medication adherence in schizophrenia patients in outpatient clinics at mental hospitals in Indonesia. This research uses a quantitative design with a cross sectional study approach. The number of samples was 195 respondents using the systematic random sampling method. Data collection uses 4 instruments consisting of 4, namely Demographic Data, BCIS, ISMI-10, MMAS. Bivariate analysis in this study used the Man-Whitney test and Chi-Square test, and multivariate analysis used logistic regression in backward Wald modeling. The results of the multivariate research found self-review (p=0.000, OR=5.747), and self-stigma (p=0.000, OR= 4.814). The factor that has the most influence on adherence to taking medication in schizophrenia patients is self-awareness with an OR value of 5.747, which means that patients with high self-awareness are 5.747 times more likely to comply with taking medication. It is hoped that nurses will focus more on improving their abilities and skills in providing care to schizophrenic patients with one of the main focuses of care being increasing insight into patients.